Planning for a 5-Story Hotel in Subarang Batuang Village, Payakumbuh City - Puja Maike; Elvi Syamsuir; Fatma Ira Wahyuni (LEADER: Civil Engineering and Architecture Journal, 2025)
Planning of a Hotel Building in Payakumbuh City. The project is located on Diponegoro Street, Subarang Batuang Subdistrict, West Payakumbuh District, Payakumbuh City. The building consists of 5 floors and is equipped with stairs and an elevator. The superstructure uses reinforced concrete construction with a concrete strength of 25, deformed reinforcing steel with a yield strength of 420, and plain reinforcing steel with a yield strength of 280. The substructure uses bored pile foundations with a depth of 7.2 m. The structural design of the building refers to the following standards: SNI 2847-2019 Structural Concrete Requirements for Buildings and Commentary, SNI 1727-2020 Minimum Design Loads and Associated Criteria for Buildings and Other Structures, SNI 1726-2019 Seismic Design Requirements for Buildings and Non-Building Structures, SNI 2052-2017 Steel Reinforcement for Concrete, Load Design Guidelines for Houses and Buildings (1987), and SNI 8900-2020 Simplified Design Guidelines for Reinforced Concrete Buildings. Based on the structural analysis, the following dimensions were obtained: slab thickness of 12, roof slab thickness of 10 cm, main beam dimensions 30/60 cm, primary main beam dimensions 35/70 cm, secondary beam dimensions in the 25/40 cm, column dimensions 60/60 cm, bored pile foundation diameter 80 cm.